Situational awareness (perception) assessment of ATC monitoring via brain eye measures - Lai, Marissa Shi Lin (Nanyang Technological University, 2021)
With the increasing use of technology in ATC systems and fluctuations in global air traffic volume, there would be changes to the scope of the Air Traffic Controller’s duties. Hence there is a need to further study situational awareness to understand the limitations of human performance and enhance safety and standards in aviation. While much work has already been done in studying situational awareness, the increasing availability of modern tools has opened up possibilities for new research techniques which could uncover new insights to enhance current findings. Eye tracking has been widely used in the field of situational awareness for air traffic control and there has been some separate studies that used electroencephalogram data. However, research involving the combination of brain-eye tracking is yet to be established. Therefore, this study aims to investigate the physiological signals associated with Level 1 situational awareness, perception. In the first part of this study, an experiment that will be conducted on a number of subjects to test Level 1 situational awareness, perception. In the experiment, their eye movements and brain activity will be tracked. From the subjects’ responses and performance in the tasks, their degree of situational awareness will be measured. Thereafter, the measure of situational awareness will be linked to the eye and brain data to identify the physiological signals. The findings of this study reveal that having situational awareness would require a threshold of fixations (duration or instances) on the information of interest, though the converse does not hold as demonstrated by several factors in the experiment. When the subjects are trying to pay more attention, spikes in their cognitive activity were observed. This study shows that there is potential in using this integrated technique to study situational awareness. It should be noted that the physiological signals found in this study may be different for the higher levels of situational awareness (comprehension and projection). Thus, it is recommended to fine-tune some aspects of this integrated technique before applying it to study the higher levels of situational awareness (comprehension and projection).